Assessing risk of the natural regeneration of introduced conifers or wilding spread - Ledgard, N.J. (New Zealand Plant Protection, 2008)
Two decision support systems (DSS) have been developed to assess (a) the threat of introduced conifer (wilding) spread from new plantings and (b) the risk of wildings establishing at any particular site Scores (04) are given for risk factors related to the species involved their spreading vigour (includes seedling growth rate age of coning seed production and seed weight) palatability siting of the parent seed trees and vegetation cover and land use particularly downwind of the seed source The maximum possible score is 20 and scores above 12 (DSSa) and 14 (DSSb) indicate high levels of risk The two DSSs can be used by land managers to quickly assess the likely risk of wilding spread and to test how they might lower the risk by changing input factors In this way spread risk can be mitigated or avoided by good decisionmaking prior to unwanted wilding spread occurring